Strengthening Teachers' Digital Literacy Capacity Through A Scratch Visual Programming Mentoring Model In Developing Learning Media - Anis Farida Jamil; Arif Hidayatul Khusna; Dwi Priyo Utomo (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2026)
learning. However, preliminary observations showed that only 20% of teachers at SMA Muhammadiyah 3 Pandaan had developed interactive media, and most were unfamiliar with Scratch. This community service aimed to improve digital literacy through Scratch-based mentoring involving 11 participants (10 teachers and 1 staff member). The method included socialization, preparation, hands-on training, and evaluation using pre- and post-training questionnaires with a four-point Likert scale to ensure the validity of competency perception measurement. The results showed a significant improvement: in the pre-test, only 9% (1 out of 11) were familiar with Scratch, but after the training, 100% of participants reported being able to develop interactive learning media independently and understand programming logic. Furthermore, 100% of participants confirmed an increase in their digital literacy regarding content creation. These findings demonstrate that hands-on training is quantitatively effective in transforming teachers' digital competence.